Mechanics and functional consequences of nuclear deformations - Kalukula, Yohalie; Stephens, Andrew D.; Lammerding, Jan; Gabriele, Sylvain (Nature reviews. Molecular cell biology, 2022)
As the home of cellular genetic information, the nucleus has a critical role in determining cell fate and function in response to various signals and stimuli. In addition to biochemical inputs, the nucleus is constantly exposed to intrinsic and extrinsic mechanical forces that trigger dynamic changes in nuclear structure and morphology. Emerging data suggest that the physical deformation of the nucleus modulates many cellular and nuclear functions. These functions have long been considered to be downstream of cytoplasmic signalling pathways and dictated by gene expression. In this Review, we discuss an emerging perspective on the mechanoregulation of the nucleus that considers the physical connections from chromatin to nuclear lamina and cytoskeletal filaments as a single mechanical unit. We describe key mechanisms of nuclear deformations in time and space and provide a critical review of the structural and functional adaptive responses of the nucleus to deformations. We then consider the contribution of nuclear deformations to the regulation of important cellular functions, including muscle contraction, cell migration and human disease pathogenesis. Collectively, these emerging insights shed new light on the dynamics of nuclear deformations and their roles in cellular mechanobiology. Nuclei are subject to various deformations, being pulled, pushed, squeezed and stretched by a plethora of intracellular and extracellular forces. Recent work is unravelling how nuclei sense and respond to these deformations, including with changes in genome organization and function, cell signalling, and cell mechanics.